"There's a stopgap in the conversation": LGBTQ + mental health care and community connection in a semi-rural county. Issue 1 (2nd January 2022) - Bettergarcia, Jay; Wedell, Emma; Shrewsbury, Amanda M.; Thomson, Bonnie Rose
Abstract: Introduction: LGBTQ + people face barriers accessing affirming mental health care in semi-rural communities. Little research has addressed the unique barriers, needs, and experiences of LGBTQ + communities, including the intersection of factors including community connectedness that may buffer distress. Method: This qualitative study comprised focus groups of LGBTQ + youth and adults living in a semi-rural county. Result: Thematic analysis identified six themes and sixteen subthemes focused on experiences in the local community and with mental health providers. Conclusion: Living in a semi-rural community may impose additional barriers to receiving affirming care and building necessary supportive community networks for LGBTQ + people.